2023
DOI: 10.1080/0886022x.2023.2228924
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prognosis for coronavirus disease 2019 among 131 hemodialysis patients during the Omicron variant epidemic

Abstract: The present study evaluated the presentations and outcomes of coronavirus disease 2019 (COVID-19) among patients undergoing maintenance hemodialysis (MHD) and the impact of the Omicron BF.7 variant. Adult patients (age ≥ 18 years), who underwent MHD (dialysis vintage ≥ 3 months) at the Hemodialysis Center at Beijing Tsinghua Changgung Hospital between December 2022 and January 2023, were included based on predefined eligibility criteria. Clinical and laboratory characteristics were retrospectively collected. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
3
1
0
Order By: Relevance
“…Bao et al found that in 102 hemodialysis patients, 12 (11.8%) died [ 13 ]. Wen found that the mortality was 5.7% which was similar with our study [ 14 ]. The omicron variant was associated with less severe disease than the delta variant but still resulted in substantial morbidity and mortality, especially among hemodialysis patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Bao et al found that in 102 hemodialysis patients, 12 (11.8%) died [ 13 ]. Wen found that the mortality was 5.7% which was similar with our study [ 14 ]. The omicron variant was associated with less severe disease than the delta variant but still resulted in substantial morbidity and mortality, especially among hemodialysis patients.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the previous studies, older patients tended to show a poorer prognosis [ 14 , 20 ]. Several previous studies have found that hyponatremia was associated with an increased death risk in MHD patients [ 21 23 ].…”
Section: Discussionsupporting
confidence: 86%
“…Type I respiratory failure was present in all severe/critical illness cases, even requiring mechanical ventilation, and hypoxemia serves as a rapid diagnostic indicator for severe/critical illness cases of COVID-19 infection. [36] Few reported studies have used the ORF1ab and N genes as predictive indicators of disease severity, with most studies indicating age, fever, and hypoxemia as strong predictive indicators for disease progression, [37] thereby aligning with observations in this study. A prediction model was established to predict and identify the probability of critical classification of MHD patients at an early stage, thereby allowing for earlier interventional treatment.…”
Section: Discussionsupporting
confidence: 82%
“… 7 17 18 Similarly, low prealbumin levels, which indicate malnutrition and poor overall health status, have been previously associated with adverse outcomes in various diseases. 17 Recognising these risk factors in the context of HD patients with SARS-CoV-2 infection delivers significant insights for risk stratification and possible interventions in this susceptible population. These findings emphasise the importance of targeted monitoring and management strategies in this high-risk population.…”
Section: Discussionmentioning
confidence: 99%